Editor's Choice – Open Thoracic and Thoraco-abdominal Aortic Repair in Patients with Connective Tissue Disease. (November 2017) - Keschenau, Paula R.; Kotelis, Drosos; Bisschop, Jeroen; Barbati, Mohammad E.; Grommes, Jochen; Mees, Barend; Gombert, Alexander; Peppelenbosch, Arnoud G.; Schurink, Geert Willem H.; Kalder, Johannes; Jacobs, Michael J.
Abstract : Objective/Background: The aim is to present current results of open complex aortic repair in patients with connective tissue disease (CTD). Methods: This was a retrospective cross-border, single centre study. From February 2000 to April 2016 72 aortic operations were performed on 65 patients with CTD (41 male, median age 41 years [range 19–70 years]). Fifty-six patients (86%) underwent at least one previous aortic repair (71 open, four endovascular), including 33 patients (51%) operated before at the site of the procedure reported here. The open procedures, counting eight emergency operations (11%), included aortic arch revision ( n = 1; 1%), descending thoracic aortic repair ( n = 11; 15%), TAAA type I repair ( n = 12; 17%), type II repair ( n = 29; 40%), type III repair ( n = 12; 17%), and type IV repair ( n = 5; 7%). Simultaneous repair of the ascending aorta and/or the aortic arch was performed in two (3%) and eight cases (11%), respectively. Seven patients (10%) underwent staged procedures. Median follow-up was 42 months (0.5–180 months). Results: The in hospital mortality was 14% ( n = 9) as a result of haemorrhage ( n = 3/9), neurological ( n = 3/9), cardiac ( n = 2/9), and pulmonary ( n = 1/9) complications. Paraplegia and paraparesis occurred in one (2%) and three patients (5%), respectively. Seven patients (11%) required temporary dialysis; none needed permanent dialysis. Major complications were revision surgery for bleeding or haematoma ( n = 20/65), sepsis ( n = 10/65), myocardial infarction/severe cardiac arrhythmia ( n = 2/65), stroke ( n = 2/65), as well as multiorgan failure, abdominal compartment syndrome, mesenteric and peripheral ischaemia (all n = 1/65). Multivariate analysis identified an operating time > 7 hours ( p = .006) as an independent predictor of increased mortality. Freedom from re-intervention was 85%, 1 year survival was 80%, and overall survival was 75%. Conclusion: Open TAA(A) repair is a durable therapy for patients with CTD. Often being performed as revision surgery, it can be associated with relevant risks and should therefore be reserved for specialised centres. Staged procedures and thus reducing operating time, if applicable, should be preferred.